Pelatihan Google Workspace sebagai Sistem Manajemen Pengetahuan di TK Islam At-Tin - Rifka Dwi Amalia; Nurul Afifah Arifuddin; Radinal Setyadinsa (Pusat Riset dan Inovasi Nasional, 2025)
This community service program is designed to address the need for digitalization in administrative management and improve digital literacy in schools. The main focus of the activity is training on the use of Google Workspace as an integrated knowledge management system to improve work efficiency and collaboration among staff. Problems faced by schools include the continued use of manual administrative systems and a low understanding of how to use digital platforms. The training was conducted as a workshop with a learning-by-doing approach, allowing participants to learn directly and contextually. The training material covered the operation of various Google Workspace features, such as Google Forms, Sheets, Calendar, Docs, Drive, and Meet. This activity was designed so that participants not only understand the function of each application but also are able to integrate them into daily administrative activities. The training evaluation was conducted through pre- and post-tests, which showed a significant increase in participants' technical understanding. In addition to improving digital competency, this training also encouraged a shift in work culture towards a more collaborative, efficient, and data-driven one. The program's success demonstrates that digital transformation in educational environments can be achieved through an educational, participatory approach tailored to local needs. With positive results, this activity has the potential to be replicated in other educational institutions as a sustainable strategy for cloud-based administrative management. This training is proof that adopting digital technology in schools can strengthen administrative governance comprehensively and sustainably.